Constructing “Ideal Victim” Stories of Bosnian War Survivors - Goran Basic (Social Inclusion, 2015)
Previous research on victimhood during and after the Bosnian war has emphasized the importance of narratives but has not focused on narratives about victimhood or analyzed post-war interviews as a competition for victimhood. This article tries to fill this gap using stories told by survivors of the Bosnian war during the 1990s. In this analysis of the retold experiences of 27 survivors of the war in northwestern Bosnia, the aim is to describe the informants’ portrayal of “victimhood” as a social phenomenon as well as analyzing the discursive patterns that contribute to constructing the category “victim”. When, after the war, different categories claim a “victim” status, it sparks a competition for victimhood. All informants are eager to present themselves as victims while at the same time the other categories’ victim status are downplayed. In this reproduction of competition for the victim role, all demarcations that were played out so successfully during the war live on.